Bar buckling in ductile RC walls with different boundary zone detailing: Experimental investigation. (1st November 2019) - Tripathi, Mayank; Dhakal, Rajesh P.; Dashti, Farhad
Highlights: Quasi-static reversed cyclic testing of slender RC walls. Effect of bar buckling on the deformation capacity of RC walls. Effect of boundary zone detailing on buckling tendency of longitudinal reinforcing bars. Design of transverse reinforcement to restrict bar buckling in slender RC walls. Abstract: The performance of reinforced concrete (RC) structural walls during the past earthquakes in New Zealand (2010–11) and Chile (2010) have highlighted the susceptibility of these critical structural components to several undesirable modes of failure. One such failure mode is premature buckling of the longitudinal reinforcing bars, which has also been observed in experimental tests of flexurally-dominant structural walls. This paper presents the results of an experimental program investigating the effects of transverse reinforcement detailing on buckling resistance of longitudinal reinforcement located in the boundary regions of RC structural walls. Three large-scale rectangular walls with different boundary zone transverse reinforcement detailing were tested under in-plane cyclic loading. The effects of these three types of detailing are reported in terms of drift capacity, buckling length of the longitudinal bars and cumulative energy dissipation capacity of the specimens. The test results confirm that bar buckling modes depend on transverse reinforcement detailing, which consequently also influences the ultimate flexural deformation capacity of ductile walls. By comparing the responses of the tested wall specimens, the inadequacy of code-compliant transverse reinforcement to restrain bar buckling is discussed and the effect of improved transverse reinforcement detailing (designed using a mechanics-based approach) on deformation capacity of slender walls is scrutinised.